Germline polymorphisms and survival of lung adenocarcinoma patients: A genome‐wide study in two European patient series. Issue 5 (19th September 2014) - Galvan, Antonella; Colombo, Francesca; Frullanti, Elisa; Dassano, Alice; Noci, Sara; Wang, Yufei; Eisen, Timothy; Matakidou, Athena; Tomasello, Luisa; Vezzalini, Marzia; Sorio, Claudio; Dugo, Matteo; et al.
<x xml:space="preserve">Abstract</x> In lung cancer, the survival of patients with the same clinical stage varies widely for unknown reasons. In this two‐phase study, we examined the hypothesis that germline variations influence the survival of patients with lung adenocarcinoma. First, we analyzed existing genotype and clinical data from 289 UK‐resident patients with lung adenocarcinoma, identifying 86 single nucleotide polymorphisms (SNPs) that associated with survival (p < 0.01). We then genotyped these candidate SNPs in a validation series of 748 patients from Italy that resulted genetically compatible with the UK series based on principal component analysis. In a Cox proportional hazard model adjusted for age, sex and clinical stage, four SNPs were confirmed on the basis of their having a hazard ratio (HR) indicating the same direction of effect in the two series and p < 0.05. The strongest association was provided by rs2107561, an intronic SNP of PTPRG, protein tyrosine phosphatase, receptor type, G; the C allele was associated with poorer survival in both patient series (pooled analysis logeHR = 0.31; 95% CI: 0.15–0.46, p = 8.5 × 10−5). PTPRG mRNA levels in 43 samples of lung adenocarcinoma were 40% of those observed in noninvolved lung tissue from the same patients. PTPRG overexpression significantly inhibited the clonogenicity of A549 lung carcinoma cells and the anchorage‐independent growth of the NCI‐H460 large cell lung cancer line. These four germline variants represent promising candidates that, with further study, may help predict clinical outcome. In addition, the PTPRG locus may have a role in tumor progression.